Therapy to improve sleep quality in ICU patients - Jesslyn Khoirunnisaa Jayanthi; Dian Hudiyawati (Jurnal Berita Ilmu Keperawatan, 2019)
Patients in intensive care units (ICU) are at risk of sleep disorders. Patients in Intensive Care Unit (ICU) with a history of cardiovascular disease, for example Coronary Heart Disease if have poor sleep quality can affect the healing process. This study aims to identify and analyze the positive effects of using Eyemask, Earplug and Dhikr Therapy on sleep quality in ICU patients. The research methods used are literature reviews on national and international articles published in the last 5-10 years. The use of Eye Mask and Ear Plug therapy and Dhikr Therapy can be applied as a supportive therapy for patients with sleep disorders in intensive care unit(ICU).